(untitled) (Al-Academy, 2018)
The aesthetic and technical expertise help in producing the artistic work and achieving results in aesthetic formulations that reflect the aesthetic and expressive dimensions and the reflective dimensions of the pottery, surpassing its traditions, asserting its active presence in life, cherishing it even when it breaks or get damaged by employing techniques that are originated from the Japanese environment. The research problem is to study how ( Kintsugi) technique and similar techniques are used to create new rebirths of pottery pieces after being exposed to external influences that cause them to break in addition to the presence of Japanese thought as a pressurizing incentive to maintain the permanence of the porcelain and cherishing it. The research is important as a reference to the technology of contemporary pottery, enriching the library, and as a source for the scholars and researchers in the field of Japanese pottery. The aim of the research is to identify how the (Kintsugi) technique was used in facing the stresses exerted on the ceramic pieces and the pressurizing thought that motivates it. The research is concerned with the Japanese porcelain products (which was subjected to stress that cause it to break) and treating it by the (Kintsugi) technique. The results showed how the (kintsugi) technique and the techniques derived from it worked in reconstructing the ceramic pieces and creating new entities to meet the pressure of the (wabi-sabi) philosophy, which accepts things with their defects after being subjected to the constant change of status as a characteristic of existence. It sees beauty in imperfection